Pengaruh Konsentrasi BAP (Benzil Amino Purin) terhadap Multiplikasi Subkultur Tunas Pisang Kepok Timbatu - Hardarani, Nofia; Karina, Jessa; Susanti, Hilda (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
White kepok bananas are known to the people of Tabunganen District, Barito Kuala Regency, South Kalimantan as kepok timbatu. Kepok timbatu bananas have the potential to be developed as a raw material banana flour so they have the potential to be widely cultivated. This will have an impact on the need for seeds on a large scale. The need for banana plants itself has an obstacle, namely the limited availability of plant seeds. The solution to overcome this problem is to use micropropagation techniques. This technique can produce a lot of seeds in a short time. The success of which is influenced by using cytokinin growth regulator, such as BAP. BAP is widely used in tissue culture to stimulate shoot formation and multiplication. The aims of this research were to determine the effect of BAP concentration and the best BAP concentration on the multiplication of timbatu banana shoot subcultures. The research was designed using a Completely Randomized Design (CRD) with one factor, i.e. BAP concentration (3, 5, 7, and 9 mg L-1), with 5 replications for each treatment, so there were 20 treatment units. Each experimental unit consisted of 4 bottles, so there were 80 planting bottles. Observations including time browning appeared, percentage of browning, time shoots appeared, number of shoots, number of leaves, number of roots and shoot height. The result showed that there was no significant effect of BAP concentration to all observed variables.